基于UG软件的弧面分度凸轮的3D建模与传动固有频率分析 - 余振华; 许朝山; 陈丽华 (Jixie chuandong)
By using the modeling and analysis function of UG,the globoidal indexing cam design and working condition analysis is carried out,the cam drive vibration frequency and vibration models are obtained.The influence materials on the natural frequency is analyzed and a new method is provided for the design and research of these cam.